2020
DOI: 10.2174/1385272823666191029115623
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin Based Nanosponges in Organic Synthesis

Abstract: The particular β-cyclodextrin 3D structure, with its hydrophilic surface and apolar cavity, has enabled to partially or totally encapsulate hydrophobic molecules of appropriated size and shape in aqueous solution as well as in solid-state through the formation of a reversible host–guest complex. Accordingly, β-cyclodextrin based nanosponges have been prepared and used in previous years for the synthesis of organic compounds. In this review, we are going to mention some of the recent reports on the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the self-assembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9]. Although reviews have also examined the application of this approach in various industrial fields [17][18][19][20][21], no reports have examined its applicability to automotive paints. However, since cyclodextrin, which tends to be used for these inclusion compounds, has high hydrophilicity, it is presumed that the compounds described in these reports would not satisfy the high-performance requirements of automotive paint films.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the self-assembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9]. Although reviews have also examined the application of this approach in various industrial fields [17][18][19][20][21], no reports have examined its applicability to automotive paints. However, since cyclodextrin, which tends to be used for these inclusion compounds, has high hydrophilicity, it is presumed that the compounds described in these reports would not satisfy the high-performance requirements of automotive paint films.…”
Section: Introductionmentioning
confidence: 99%
“…24−27 The pore structure, linker choice, βCD/crosslinker proportion, and synthetic conditions allow for the formation of βCD nanosponges with varying surface areas, porosities, ζ-potentials, and solubilities. 23,28,29 Thus, combining βCDs with nanocellulose is highly beneficial for different applications with notable synergy between the two materials for excellent biocompatibility, low cytotoxicity, efficient polymerization, and versatile functionalization. 16 Cellulose is inert in the human body and eventually is excreted.…”
Section: Introductionmentioning
confidence: 99%
“…The unique supramolecular inclusion complexes of βCD and their high complexing potential with cross-linkers increase their hydrophilicity and encapsulation efficiency. βCDs are largely preferred for nanosponge preparation due to their easy availability, high entrapment efficiency, protection against high temperatures and oxidation, amphiphilic loading, and low association constants, enabling encapsulation and controlled release of guests. The pore structure, linker choice, βCD/cross-linker proportion, and synthetic conditions allow for the formation of βCD nanosponges with varying surface areas, porosities, ζ-potentials, and solubilities. ,, Thus, combining βCDs with nanocellulose is highly beneficial for different applications with notable synergy between the two materials for excellent biocompatibility, low cytotoxicity, efficient polymerization, and versatile functionalization . Cellulose is inert in the human body and eventually is excreted.…”
Section: Introductionmentioning
confidence: 99%
“…Other attractive features include high availability, easy synthesis, large-scale production, and harmlessness. For these reasons, in recent years, cyclodextrins (CDs) and their derivatives have attracted much attention and have wide applications in various fields of science and technology 24 , including biosensors 25 , 26 , pharmacy, food industry, decomposition chemistry 27 , agriculture, and possible environmental protection 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%